Unlocking Potential: Childcare Services and Refugees' Integration, Employment and Well-Being - Ludovica Gambaro; Mathias Huebener; Sophia Schmitz; C. Katharina Spieß (Institute of Labor Economics (IZA), 2024)
In armed conflicts, it is common for women, children, and the elderly to flee, leaving the men behind. While refugee women face particular challenges in caring for children in host countries, there is only limited evidence on the impact of childcare services on their integration. This paper examines the role of childcare services in the integration, employment, and well-being of refugee mothers. We focus on the displacement caused by the Russian invasion in Ukraine. Our analysis is based on a unique, large, and representative panel data set of Ukrainian refugees in Germany. We find a strong correlation between childcare attendance and the participation of refugee mothers in language courses, labour market activity, and social interaction. To establish causality, we leverage exogenous regional differences in childcare availability and excess demand. Our results reveal significant positive effects of childcare services on the participation of refugee mothers in language and integration programs, as well as employment and their interactions with Germans. However, we find no effects on maternal well-being. Our findings emphasize the importance of providing childcare services to refugee mothers to facilitate their integration.
Keywords: I26; J13; J15; 330; childcare services; refugees; forced migration; integration; employment; Ukraine